A FRAMEWORK OF PRACTICAL ECONOMIC INDICATORS FOR TRANSIT-ORIENTED DEVELOPMENT (FPEI-TOD): IDENTIFICATION AND EXPERT VALIDATION - Ali, Nurulhuda; Hamzah, Hasniyati; Alias, Anuar; Muhamad, Ismail (PLANNING MALAYSIA, 2024)
Transit-Oriented Development (TOD) can be one of the tools to achieve sustainable urban management (SUM), as promoted by SDG11 on Sustainable Cities and Communities. In the context of Malaysia, TOD is seen as a potential solution to urban challenges, i.e., traffic congestion, pollution, rising cost of living, lack of employment opportunities, and the prevalence of crime. However, in determining a balanced approach to SUM, TODS must have a framework of indicators that can be used to guide its implementation so the three sustainable development dimensions are catered for, particularly the economic dimension. A review of previous studies and literature on TOD revealed a dearth of studies on economic indicators for TOD in Malaysia. Using the sequential mixed methods approach, this research aimed to improve the current implementation of TOD for sustainable urban management by proposing a framework for practical economic indicators of TOD and endeavouring to close the gap in practical TOD assessment in Malaysia. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) were used to extract the economic indicators before deploying a questionnaire survey for experts’ validation. A total of 48 economic indicators that are practical to implement for TOD were produced based on the experts’ opinions. These indicators would serve as measuring tools for ensuring sustainable TODs that not only provide greater transit facilities but are also resilient in facing future urban challenges.